Pemikiran Tun Dr. Mahathir bin Mohamad Abdul Mua'ti @ Zamri bin Ahmad.. - Abdul Mua'ti. (Penerbit Universiti Malaya, 2007)
Analysis of Mahathir Mohamad's speeches on political, economic, sociocultural, and international issues in Malaysia delivered to UMNO's General Assembly from 1982 up to 2003.